Sally Rooney, Normal People (Londra, Faber & Faber, 2018, 266 pp. ISBN 978-0-571-33465-0) (Altre Modernità, 2020)
Sally Rooney, Normal People (Londra, Faber & Faber, 2018, 266 pp. ISBN 978-0-571-33465-0)di Federico Prina